Prognostic Value of Arterial Blood Gases in Predicting ICU Mortality in Patients Under General Anesthesia - Abdul Waheed, Zahid Hussain, Ahmed Usman, Bushra Amin, Sabir Khan, Muhammad Zubair, Aishwarya Preman, Khadija Abdul Hameed Palekar, Affan Mudassar, Jachi Chituru-Moses, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Arterial blood gas parameters during general anesthesia possess prospective value in forecastingintensive care unit mortality. This experimental investigation evaluated the prognostic significance of intra-operative arterial blood gases—specifically pH, PaO₂, PaCO₂, bicarbonate, base excess,and lactate—in adult patients undergoing